Ophthalmic manifestations of psoriasis - Kritika Katoch; Ratan Kumar Sharma; Vikram mahajan; Rajeev Tuli (Delhi Journal of Ophthalmology)
Psoriasis is a common chronic inflammatory and proliferative condition of the skin associated with systemic manifestations. The relationship between the eye and psoriasis has been recognized for decades, but the precise eye manifestations in patients with psoriasis and psoriatic arthritis are only recently coming to light. Ocular involvement occurs in 10% of patients with psoriasis. Ophthalmic manifestations include blepharitis, dry eye, meibomian gland dysfunction, nonspecific conjunctivitis, punctate keratitis, corneal recurrent erosions, vascularisation, ulceration, scarring and even melting. Anterior uveitis is another psoriasis associated manifestation involving 7% to 25% of patients with psoriatic arthritis. Retinal vasculitis, cystoid macular edema, and papillitis are other uncommon changes seen. Various topical and systemic therapies used to treat psoriasis too can affect eyes, which includes conjunctiva hyperaemia, dry eye, blepharitis, blepharoconjunctivitis, keratitis, corneal opacities, cataract, and deceased night vision.